Certified Corona-immunity as a resource and strategy to cope with pandemic costs - Reiner Eichenberger; Rainer Hegselmann; David Savage; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2020)
A pandemic is not only a biological event and a public health disaster, but it also generates impacts that are worth understanding from a societal, historical, and cultural perspective.In this contribution, we argue that as the disease spreads, we are able to harness a valuable key resource, namely people who have immunity to Corona. This vital resource must be employed effectively, it must be certified, it must be searched for, it must be found, and it may even be activelyproduced. We discuss why this needs to be done and how this can be achieved. Our arguments not only apply to the current pandemic, but also to any future rapidly spreading, infectious disease epidemics. In addition, we argue for awareness of a secondary non-biological crisis arising from the side effects of pandemic reactions. There is a risk that the impacts of the secondary crisis could outweigh that of the biological event from a health and societal perspective.
Keywords: 330; Coronavirus; Standardisierung; Gesundheit